Group portrait of the attendees of the California Conference of the Epworth League Institute - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of the attendees of the 1937 California Conference of the Epworth League Institute, held in Humboldt, California. Several conference members can be seen holding up signs denoting their local chapter's area, city, or county of origin.